An epitope in human immunodeficiency virus 1 reverse transcriptase recognized by both mouse and human cytotoxic T lymphocytes. - Hosmalin, A (1990)
T-cell-mediated cytotoxicity may play an important role in control of infection by the human immunodeficiency virus (HIV). In this study, we have identified and characterized a relatively conserved epitope in the HIV-1 reverse transcriptase recognized by murine and human cytotoxic T cells. This epitope was identified using a murine antigen-specific CD8+ class I major histocompatibility complex-restricted cytotoxic T-cell (CTL) line, a transfected fibroblast cell line expressing the HIV-1 pol gene, recombinant vaccinia viruses containing different truncated versions of the pol gene, and overlapping synthetic peptides. The optimal antigenic site was identified as residues 203-219 by synthesizing extended or truncated peptide analogs of the antigenic fragment. The optimal peptide was then tested for sensitization of autologous Epstein-Barr virus-transformed B-cell targets for killing by fresh human peripheral blood mononuclear cells. It was recognized by CTLs from several HIV-seropositive patients but not from any seronegative donor. Therefore, this peptide is a good candidate for inclusion in an AIDS vaccine. This study demonstrates that the same CTL epitope can be seen by murine and human CD8+ CTLs, as previously demonstrated for epitopes recognized by CD4+ helper T cells, and suggests the utility of screening for immunodominant CTL epitopes in mice prior to carrying out studies in humans.